Assessment of the Improvement Orthodontic Treatment with Removable Orthodontic Appliance in RSGM UMY using Par - Dr.drg. Tita Ratya Utari, Sp.Ort, Yuniar Tri Wahyuti (Fakultas Kedokteran UMY, 2014)
This study is aimed to know the imrovement of removable orthodontic appliance in RSGMP UMY using PAR index. Subjects of this study are 130 dental casts pre treatment and last traetment from the patiens who has been traeted by internship student in RSGMP UMY in the period of December 2009 until September 2012.